The Effect of The Molase With Different Amounts of The Biofloc on The Growth of Catfish (Clarias gariepinus) - Sepri Ariansyah; Rusliadi Rusliadi; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            Research was carried out on the 13 April to 22 May 2018 in the Aquaculture Technology Laboratory, Department of Aquaculture, Faculty of Fisheries and Marine University of Riau. The purpose of this study to determine the amount of molase for the growth of catfish (Clarias gariepinus) the biofloc. The research method which is using method of random (RAL) by a factor which consists of four stages of treatment used the C 10 (Molase 21 g), C 15 (Molase 35 g), C 20 (molase 48 g) and C 25 (molase 62 g). For the next 40 days the maintenance of the best in the provision of molase 62 g in the growth of seeds is absolute of 6,38 g, the length of the absolute 6,62 cm, the growth rate of specific 4,56%, efficient feed of 95,43%, survival rate  to 51,11% and volume floc 8,57 ml/l. And the quality of water for research which is the temperature 26-29,20C, pH 7,1-7,4, dissolved oxygen 3,63-6,63 ppm and ammonia 0,003-0,033. Keyword :Clarias gariepinus, Biofloc, Molase